2012
DOI: 10.3329/jemc.v1i1.11137
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ABO and Rh-D Blood Group Systems between the Garo Tribal People of Mymensingh and General People of Dhaka City

Abstract: Background: The distribution pattern of ABO and Rh-D blood group in our country including the tribal people is not fully established as elaborated and large scale studies have not been carried out on it. Therefore this study was designed to observe the distribution pattern of ABO and Rh-D blood groups among the Garo tribes of Mymensingh and general people of Dhaka city. Objectives: To determine and to compare the distribution pattern of ABO and Rh-D blood groups among the Garo tribal people of Mymensingh and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Our results showed that young age groups (18 to 25 years) were more enthusiastic about blood donation, concurring with previous findings. 1,16,17 Additionally, the vast majority of the donors were males. This could possibly be attributed to the fact that in Bangladesh, females are more occupied with household work and hence have less time for blood donation along with rejection from donation according to selection criteria like running menstruation, iron deficiency anaemia, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Our results showed that young age groups (18 to 25 years) were more enthusiastic about blood donation, concurring with previous findings. 1,16,17 Additionally, the vast majority of the donors were males. This could possibly be attributed to the fact that in Bangladesh, females are more occupied with household work and hence have less time for blood donation along with rejection from donation according to selection criteria like running menstruation, iron deficiency anaemia, etc.…”
Section: Resultsmentioning
confidence: 99%